Role of parents, teachers at home and school in prevention of female sexual abuse: an analysis - Nainar, Anithathamaraiselvi A.; Ramasamy, Sivapriya; Shanmugam, Mekala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Sexual assault is an act performed by one person on another without the person’s consent or on a victim who is incapable of giving consent. The purpose of this article is to analyze the female sexual assault cases reported in one year –and the role of parents, teachers, at home and school in prevention of child sexual abuse. Methods: Data of victims who were admitted in GDMCH in the department of obstetrics and gynaecology in the year 2020 were collected from the medico legal register retrospectively and analyzed. Results: Age wise distribution showed 70% of cases were in the age group 15-19 years. 57% of assaults were with consent and 43% without consent. 93% of the perpetrators were known to the victim. Around 48% of the assaults were multiple episodes by a single perpetrator. The place of assault in 39% of cases was perpetrator’s house, 35% was in friend’s or relative’s house. Conclusions: 86% of the victims were <19 years of age, hence, educational awareness services are to be given to high school students and teachers .School authorities and teachers should implement strict vigilance against improper use of the internet and mobile phones by the students. Most common location of assault was the perpetrator's house (39%), followed by their friend’s house (22%). Hence parents should take every care to watch over the child and never leave them unsupervised.